Determination of the effect of noise on the image using software - Danil L. Myasnikov; Leonid D. Lozhkin; Yulia V. Sokolova (Физика волновых процессов и радиотехнические системы, 2023)
In this paper, we study the influence of noise on images of different colors and determine the difference in the level of these influences. Values characterizing the signal-to-noise ratio in decibels are obtained. The comparison of the values obtained as a result of modeling with the values of mathematical calculations is made. The results of the work present the data learned empirically. Thanks to the use of software, a unique structure that was achieved as a result of its own writing, it was possible to carry out a number of simulations and obtain several groups of values. Computer colorimetry can rightly be called digital colorimetry. This article is intended for senior students of universities, graduate students and professionals working in the field of color reproduction, image processing, color measurements and other areas related to color perception.